Flouting of maxims in staff meetings / Bharathi Mutty - Mutty, Bharathi (2012)
This study explores the ways in which the staff of three local academic institutions flout Grice’s maxims in conversation during staff meetings. The study was conducted in two phases. The first phase was recording the staff meetings in participating institutions in two manners: overtly (the staff knew that they were being recorded) and covertly (the staff did not know they were being recorded). The second phase was to interview the staff present in the meetings to determine the reasons for them to flout the maxims during the meetings. This was done by playing the recordings to the interviewees after every meeting. Findings revealed that the staff of all the three institutions involved in this research did flout the maxims during the meetings due to several reasons. Politeness, power and social distance are few of the many reasons identified. The staff did not want to say anything that would offend the authority and thus flouted the maxims. Lack of information to answer the questions asked was also another reason to flout the maxims. It was also found that there were major differences in the ways the staff flouted the maxims when they were aware of the recording and when they were not aware of the recording. For instance, the Maxim of Manner was flouted frequently during overt recordings to avoid the researcher from recording any sensitive issue raised in the meetings.